China’s protective diplomacy: safeguarding Vietnam’s sovereignty amidst 19th century complexities - Luan, Vu Duong; Dar, Ku Boon (Penerbit UKM, 2023)
During the 19th century, a multifaceted dynamic unfolded among China, Vietnam, and France. France’s ambitions to extend colonial control over Vietnam posed a potential threat to China’s security and regional stability. This article delves into the historical context, exploring China’s diplomatic and military strategies aimed at safeguarding Vietnam from French colonization. By analyzing historical accounts and scholarly sources, the study illuminates China’s efforts to preserve Vietnam’s sovereignty. Focusing on pivotal events, diplomatic initiatives, and military campaigns undertaken by China, the research sheds light on the perspectives of notable Chinese diplomats, including Zeng Jize, Tang Yanggeng, Chen Baozhen, and Zhang Peilun. The essay underscores China’s pivotal role in protecting Vietnam and maintaining regional security concerns. It highlights the intricate nature of managing diplomatic relations with both Vietnam and France, necessitating a delicate balance. Through a comprehensive examination of historical dynamics, this article enriches our understanding of the intricate connections between China, Vietnam, and France during this critical period.